Halal Tourism: Innovation In Halal Tourism Development Through The Implementation Of A Creative Economy Based On Theater Drama Arts In Sampuraga Mandailing Natal - Rahmat, Paisal; Affandi, Faisal; Zein, Alimansya Huri; Brt, Ainun Nisa; Apriani, Lely (Indonesian Journal for Entrepreneurial Review, 2025)
Sampuraga is a tourist destination located in Sirambas Village, West Panyabungn District, Mandailing Natal Regency, North Sumatera. The hot springs that have the legend of sampuraga are iconic. However, as time went by, touris interest in visiting dropped drastically. This research aims to provide innovation for Sampuraga tourism through the legendary Sampuraga theater drama. The date collection method in this scientific paper uses research journals, theses and research reports. . Analysis in the process in carried out with the data that has been collected, then explained again in the discussion. The data analysis proses uses the Miles and Huberman modal, namely: the data reduction stage and data presentation stage. The conculusion that can be drawn from this research is the Dreama theater can increase the number of tourists so that it can influence the increase in the creative economy fot local communities. The role of the Tourism Departement is important in analyzing the potential of sampuraga tourist attractions to produce an effective anda efficient tourism development concept to achieve sustainable halal tourism.